Trend of Chromosomal Disorders in Patients Referred for Chromosomal Analysis in Cytogenetic Lab of BPKIHS: An Institutional Based Retrospective Study - Khanal, Laxman; Koirala, Sarun; Shah, Sandip; Yadav, Prabhakar; Baral, Presha; Shrestha, Samsher (Annapurna Journal of Health Sciences, 2024)
Introduction: Chromosome abnormalities are the results of alterations in the number or structure of chromosomes causing significant human morbidity and mortality. Cytogenetic analysis is crucial in identifying these abnormalities and guiding genetic counseling and clinical management. The main objective is to describe the patients having chromosomal analysis on the basis of their demographic profile, cause of referral and referral central; and to estimate the distribution of different chromosomal aberration among those patients who underwent chromosomal analysis. Methods: All the patient referred to the cytogenetic lab of B.P Koirala Institute of Health Sciences, Nepal between 2004 and 2015 for chromosomal analysis were assessed from the record of lab. Demographic data, referring department/ clinic, patients karyotype and frequency of distribution of various karyotype was assessed. Results: Most of the patients were between 20 and 50 years old, and 64% were male. The most common reasons for referral were suspected Chronic myeloid leukemia (CML) (n=215), Down's syndrome (n=27), amenorrhea, and ambiguous genitalia. BPKMCH was the most common referral center to refer the cases in cytogenetic lab (63.7% of cases). Philadelphia-positive CML, Down's syndrome, and Turner's syndrome were the most common cytogenetic diagnoses made. Conclusion: Suspected CML was the primary reason for referral. Most patients were aged between 20 to 50 years, with males comprising 64% of the cohort. Philadelphia positive CML was the most common cytogenetic diagnosis. Referrals peaked in 2005 AD, primarily from BPKMCH.